The Influence of Individual Characteristics, Work Environment, Paternalistic Leadership Style and Competencies on Employee Performance at PT Fajar Saudara Kusuma Sebawi Mill In West Kalimantan - Suci Harira Sari Hatuina; Ida Aju Brahma Sari; Ida Aju Brahma Ratih (Journal of Social Research, 2025)
This study aims to evaluate the influence of individual characteristics, work environment, and paternalistic leadership style on employee performance and competence at PT Fajar Brother Kusuma Sebawi Mill in West Kalimantan, which operates in the palm oil, plantation, and sea transportation sectors. The research uses a quantitative approach, employing a survey method to gather data from employees. The data was analyzed using statistical techniques to identify the relationships between the variables. The results indicate that individual characteristics do not have a significant effect on employee performance or competence at PT Fajar Saudara Kusuma Sebawi Mill. However, the work environment has a significant positive impact on employee performance, while it does not affect competence. The paternalistic leadership style is found to significantly influence both employee performance and competence. Moreover, competence positively affects employee performance, highlighting the importance of improving employees' skills and abilities for enhanced work outcomes. In conclusion, the study demonstrates that while individual characteristics are not significant, the work environment and paternalistic leadership style play crucial roles in improving employee performance and competence. The results suggest that PT Fajar Brother Kusuma Sebawi Mill should focus on optimizing the work environment and leadership styles to enhance employee productivity and skills, thereby driving the company’s growth. The study provides valuable insights for companies aiming to improve their human resource management strategies, especially in the plantation and sea transportation sectors.